Response of the bGeigie Nano and CzechRad Monitors to Secondary Cosmic Radiation - Petr Kuča; Jan Helebrant; Peter Bossew (Sensors)
Ambient dose rate surveying has the objective, in most cases, to quantify terrestrial radiation levels. This is true in particular for Citizen Monitoring projects. Readings of detectors, which do not provide spectrally resolved information, such as G-M counters, are the sum of contributions from different sources, including cosmic radiation. To estimate the terrestrial component, one has to subtract the remaining ones. In this paper, we investigate the cosmic response of two particular monitors, the bGeigie Nano, which has been used extensively in the Safecast Citizen Monitoring project, and its upgraded version, the new CzechRad, which uses the same G-M detector, and show how the local contribution of cosmic radiation can be estimated.